If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -15 + 10x + 4 = 0 Reorder the terms: -15 + 4 + -12x + 10x = 0 Combine like terms: -15 + 4 = -11 -11 + -12x + 10x = 0 Combine like terms: -12x + 10x = -2x -11 + -2x = 0 Solving -11 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -2x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -2x = 0 + 11 -2x = 0 + 11 Combine like terms: 0 + 11 = 11 -2x = 11 Divide each side by '-2'. x = -5.5 Simplifying x = -5.5
| 22-(-13)=m | | 12e-4=140 | | x^3-7x^2y+6xy^2=0 | | 162(t)=88t-11t^2+30 | | -7/2j=-21 | | -4x+17=-45 | | 6x=5y-11 | | 2x-3*2=-4 | | -3x+4y=-13 | | (2-3x+4)-8x=30 | | 5(-5+x)=6(x+0.2) | | =-21x+9 | | 5y-1x=10 | | 8y+3(y-8)=6(y+1)-4 | | 2x-4=1x+3 | | 12=0.92 | | 2cos(3x)cos(x)=0 | | 7c=150 | | X-380+x^2=0 | | .08x-.1=16.7 | | 3x-5=3(x+8) | | (-52)(35)= | | -13.3p+10.52=18.28-12.9p | | r^2+4r=45 | | 2c-d=1 | | 16=-9-a | | Y=126 | | 9x+3=3(17-x) | | 5/6p=14 | | 7*p^2+56*p+112=0 | | -3a-4=33 | | 3sec(x)+4=0 |